Experimental Study of Aircraft Achieving Dutch Roll Mode Stability without Weathercock Stability - Jingcheng Fu; Jun Huang; Lei Song; Daqing Yang (International Journal of Aerospace Engineering)
Weathercock stability is usually considered essential to achieve normal flight, while the Dutch roll mode stability can still be achieved without weathercock stability which has been algebraically proved. This paper proposed a flight experiment to investigate the characteristics of an airplane with Dutch roll mode stability but no weathercock stability. Firstly, the algebraic analysis based on a standard lateral-directional mode approximation was made to demonstrate the effect of yawing stability derivative Cnβ on the Dutch roll mode characteristics. The flight experiment was organized after that using a model glider which was modified to have zero Cnβ but with marginal change on Cyβ. The convergence of Dutch roll mode in flight meets the algebraic and numerical analysis as expected. However, the difference of handling characteristics between the original and modified configurations indicates some other roles the weathercock stability plays in flight as well as some limitations of utilizing mode criterion in flight quality analysis.